2023
DOI: 10.1111/jace.18977
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic energy storage performances of La(Ni2/3Ta1/3)O3‐modified Na0.5Bi0.5TiO3 lead‐free ceramics

Abstract: Ceramic capacitors with high electrostatic energy storage performances have captured much research interest in latest years. Sodium bismuth titanate (Na0.5Bi0.5TiO3)‐based ferroelectric ceramics show great potential due to their environment‐friendly composition, high polarization, and excellent relaxor properties. However, the nonergodic relaxor state of Na0.5Bi0.5TiO3‐based ceramics hampers the decrement of remanent polarization, leading to poor energy storage performance. Herein, the (1 − x)Na0.5Bi0.5TiO3–xL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…17,46,47 The decrease of tanδ is conducive to reducing energy loss and improving η. 48 To analyze the relaxation behavior in depth, the diffusion factor (γ) is often used to describe the degree of relaxation, which is calculated by the following formula 49 :…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,46,47 The decrease of tanδ is conducive to reducing energy loss and improving η. 48 To analyze the relaxation behavior in depth, the diffusion factor (γ) is often used to describe the degree of relaxation, which is calculated by the following formula 49 :…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, with the increase of SANT, the saturation polarization is delayed and the P-E loops are refined, which can be attributed to the destruction of long-range ferroelectric order and the formation of PNRs, resulting in the fast response of small-sized domain. 48,51 In addition, the value of W rec , W t and η for 0.84NBLBT-0.16SANT ceramic at different electric fields are shown in Figure 7(B). With the increase of applied electric fields, the value of W rec gradually raises.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In addition, the long-range ferroelectric order can be severely disrupted through La doping, which will contribute to the promotion of ergodicity degree and energy storage performance. [28][29][30][31] Zhang et al reported that the ergodic degree deepened with La content in a La-doped 0.93(Na 0.5 Bi 0.5 )TiO 3 -0.07Ba(Zr 0.055 Ti 0.945 )O 3 system, which resulted in "slimmer" P-E loops and enhanced η and W rec . 29 Yu et al added La to 0.78Na 0.5 Bi 0.5 TiO 3 -0.22K 0.5 Bi 0.5 TiO 3 ceramics and discovered that the ferroelectric order was largely disrupted by La doping and converted to an ergodic relaxation state.…”
Section: Introductionmentioning
confidence: 99%
“…synthesized lead‐free La‐substituted 0.72Na0.5Bi0.5TiO3‐0.28Sr0.7Bi0.2TiO3 and showed that La addition effectively decreased the grain size and generated a large E b , achieving the optimum W rec (1.2 J/cm 3 ) for 0.005La‐substituted ceramic under an E b of 90 kV/cm 27 . In addition, the long‐range ferroelectric order can be severely disrupted through La doping, which will contribute to the promotion of ergodicity degree and energy storage performance 28–31 . Zhang et al.…”
Section: Introductionmentioning
confidence: 99%